Trademark Protection for Chinese Enterprises in the Philippines under New Media Marketing - Luo, Zhiming (Pacific International Journal, 2025)
With the rapid development of new media marketing, Chinese enterprises expanding their business in the Philippines face both opportunities and challenges in trademark protection. This paper delves into the intricate landscape of trademark protection for Chinese enterprises operating in the Philippines within the dynamic realm of new media marketing. As new media continues to reshape the marketing paradigm, Chinese companies expanding into the Philippine market encounter a unique set of opportunities and formidable challenges regarding trademark safeguarding. Through a comprehensive analysis of the current state of new media marketing in the Philippines, identification of prevalent issues and complexities in trademark protection, and the formulation of strategic recommendations, this study aims to equip Chinese enterprises with the tools necessary to navigate these challenges effectively, the article concludes by presenting a range of practical countermeasures. These strategies encompass strengthening legal frameworks, enhancing monitoring and enforcement mechanisms, fostering public awareness, and leveraging technological advancements to bolster their trademark protection efforts. By adopting these comprehensive approaches, Chinese enterprises can fortify their position in the Philippine market, ensuring their brands remain resilient against the myriad threats posed by the new media marketing era.